Audit Sistem Informasi Absensi Mesin Fingerprint Pada PT. Metal Castindo Industritama Dengan Menggunakan Framework Cobit 5 - Rizka Nurul Wahidah; Nur Lutfiyana; Vanny Fitria Ramadanti; Panji Septiyo; Rian Drefiyanto (LPPM STMIK ANTAR BANGSA, 2022)
Abstract—PT. Metal Castindo Industritama is a company engaged in investment casting, sand casting and permanent mold with cast products from steel alloys, FCD, stainless steel and aluminium. Meanwhile, PT. Metal Castindo Industritama has implemented an information system to optimize the company's operational activities. One of them is the presence of a device that is connected to a computer, namely a fingerprint machine to record employee attendance times. The process applied should have the ability to manage information, convey information, maintain information security, and protect information properly. Therefore, it is necessary to conduct an audit that aims to assess the on going IT governance. The purpose of this analysis is to estimate the level of maturity and examine the problems that exist in the way attendance information system and to provide recommendations to the company in order to optimize the available IT management. In this analysis, the capability model is used as a parameter related to the respondent's responses from the list of questions that have been made based on the COBIT framework version 5 MEA domain (Monitor, Evaluate, and Assess) as a reference. A total of 40 resource persons who participated in completing the list of questions were taken from the manager level to the operator of PT. Metal Castindo Industritama usually runs the utilization of the fingerprint machine. Based on the decisions of respondents' responses, the current capability number is 3.6 in the range of 1-4. In order to reach the necessary conclusions, a number of recommendations were made to optimize the capabilities and references for updating the fingerprint machine capabilities at PT. Metal Castindo Industritama in the future. Keywords — Attendance, Fingerprint, MEA (Monitor, Evaluate, and Assess), COBIT 5 Intisari—PT. Metal Castindo Industritama adalah perusahaan yang bergerak dibidang investment casting, sand casting dan permanent mould dengan produk cor dari paduan baja, FCD, stainless steel dan alumunium. Sementara itu, PT. Metal Castindo Industritama telah menerapkan suatu sistem informasi guna mengoptimalkan kegiatan operasional kerja perusahaan. Salah satunya dengan adanya alat yang terhubung dengan kompoter yakni mesin fingerprint untuk merekam waktu hadir karyawan. Proses yang diterapkan seharusnya memiliki kemampuan dalam hal mengelola informasi, menyampaikan informasi, menjaga keamanan informasi, dan melindungi informasi dengan baik. Maka dari itu, diperlukan melakukan audit yang bertujuan untuk menilai terkait tata kelola TI yang sedang berjalan. Tujuan dari analisa ini yaitu untuk memperkirakan tingkat kematangan dan memeriksa persoalan yang ada pada cara sistem informasi absensi serta untuk memberikan rekomendasi kepada perusahaan guna mengoptimalkan manajemen TI yang tersedia. Dalam analisa ini memakai model kapabilitas sebagai parameter berhubungan dengan tanggapan narasumber dari daftar pertanyaan yang telah dibuat bersumber pada framework COBIT versi 5 domain MEA (Monitor, Evaluate, and Assess) menjadi rujukan. Total narasumber yang berpartisipasi dalam melengkapi daftar pertanyaan diambil sejumlah 40 narasumber mulai dari level manajer hingga operator PT. Metal Castindo Industritama yang biasanya menjalankan pendayagunaan mesin fingerprint tersebut. Berdasarkan keputusan dari tanggapan responden, maka memperoleh angka kapabilitas kini sebanyak 3,6 pada rentang 1-4. Demi meraih kesimpulan yang diperlukan, maka direalisasilah sejumlah anjuran bakal mengoptimalkan kemampuan serta rujukan perbaruan kemampuan mesin fingerprint tersebut pada PT. Metal Castindo Industritama dalam masa nanti. Kata Kunci — Absensi, Fingerprint, MEA (Monitor, Evaluate, and Assess), COBIT 5.